2008
DOI: 10.1063/1.2908893
|View full text |Cite
|
Sign up to set email alerts
|

Neutron reflection from a liquid helium surface

Abstract: The reflection of neutrons from a helium surface has been observed for the first time. The 4 He surface is smoother in the superfluid state at 1.54 K than in the case of the normal liquid at 2.3 K. In the superfluid state we also observe a surface layer~200 Å thick which has a subtly different neutron scattering cross-section, which may be explained by an enhanced Bose-Einstein condensate fraction close to the helium surface. The application of neutron reflectometry described in this paper creates new and exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The SLD profile is also good replication of that shown in Ref. 6 as in this paper we have refitted the original data set with the new fitting package to check the validity of the initial model. For the scientific implications of the SLD profile 4 He mixture.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…The SLD profile is also good replication of that shown in Ref. 6 as in this paper we have refitted the original data set with the new fitting package to check the validity of the initial model. For the scientific implications of the SLD profile 4 He mixture.…”
Section: Introductionsupporting
confidence: 68%
“…5 Much later the reflection of neutrons was observed for the first time from the free surface of liquid 4 He. 6 These experiments showed that the 4 He surface is smoother in the superfluid state at 1.54 K than in the case of the normal liquid at 2.3 K. In the superfluid state a $200 Å thick surface layer was found that has a subtly different neutron scattering cross-section, which may be explained by an enhanced Bose-Einstein condensate fraction close to the helium surface.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Gas detectors filled with 3 He are commonly used for the detection of thermal neutrons, due to their high efficiency and low gamma sensitivity [1]. Standard 3 He detectors on advanced neutron scattering instruments allow us to cover a broad range of scattering angles and momentum transfer vectors Q. For neutron spectroscopy, however, the need to measure the neutron energy transfers can make the instrument design much more complicated.…”
Section: Introductionmentioning
confidence: 99%